Outcome of Percutaneous Nephrolithotomy in Patients with Spinal Cord Neuropathy - Sofimajidpour, Heshmatollah; Kolahghoci, Pooya; Gharibi, Fardin (Urology Journal, 2016)
Purpose: To investigate technical problems, complications and stone clearance rate in patients with spinal neuropathy who had undergone percutaneous nephrolithotomy. Materials and Methods: This cross-sectional study was done between 2004 and 2013 on 29 patients with both spinal cord neuropathy and kidney stones who were chosen for percutaneous nephrolithotomy in Sanandaj city, Iran. The data were obtained from patients’ medical records and were documented in a researcher-made checklist. Absolute and relative frequency, mean and standard deviation were calculated. Results: A total of 43 percutaneous nephrolithotomies were performed on 32 kidneys. In 51.7% the right kidney, in 37.9% the left kidney and in three patients (10.3%) both kidneys were involved. There were 24 patients (82.8%) with spinal cord injury. Five patients (17.2%) had spina bifida. The mean of operation time was 129.7 minutes and the mean of hospital stay was 8.3 ± 3.1 days. The mean of kidney stone size was 35.7 ± 6.1 mm (25 to 45 mm). In 58.5% of the patients, surgery lasted more than two hours. Stone clearance rates were 53.1% and 78.1% after the first and second percutaneous nephrolithotomy. Conclusion: Although patients with spinal cord injury have problems in terms of surgery and complications, percutaneous nephrolithotomy is an appropriate and safe treatment method for their kidney stones. Pre-operative counseling with a radiologist and an anesthesiologist is recommended.